A successful case of percutaneous transluminal septal myocardial ablation for left ventricular outflow tract obstruction caused by sigmoid septum - Hamana, Tomoyo (J Cardiol Cases, 2020)
A sigmoid septum is a state of angulation between the basal interventricular septum and the ascending aorta. Although considered to have no clinical importance, it may cause left ventricular outflow tract obstruction (LVOTO) in a hypercontractile state. Percutaneous transluminal septal myocardial ablation (PTSMA) is a catheter-based therapy aimed at improving drug-refractory symptoms in patients with hypertrophic obstructive cardiomyopathy. Few studies have reported the use of PTSMA for patients with LVOTO caused by sigmoid septum. We present a successful case of a 71-year-old female patient who presented with a long history of exertional dyspnea. The presence of a sigmoid septum was revealed on echocardiography. At rest, the left ventricular outflow tract pressure gradient was low and there were no signs of systolic anterior motion (SAM) of the mitral valve; however, during Valsalva maneuver, the gradient increased significantly, and SAM could be seen. We successfully performed PTSMA, resulting in a significant lowering of the pressure gradient and disappearance of SAM. The patient’s symptoms dramatically improved by the following day. <Learning objective: In some clinical settings, left ventricular outflow tract obstruction caused by sigmoid septum results in cryptogenic exertional dyspnea. This case highlights the importance of an accurate diagnosis through Valsalva maneuver during echocardiogram and demonstrates the effectiveness of percutaneous transluminal septal myocardial ablation for symptomatic sigmoid septum.>